A reference genome for the eastern bettong (Bettongia gaimardi) [version 2; peer review: 2 approved, 1 approved with reservations] - Richard J Edwards; Luke W Silver; Sam Banks; Carolyn J Hogg; Adrian D. Manning; Linda Neaves (F1000Research)
Abstract The eastern or Tasmanian bettong (Bettongia gaimardi) is one of four extant bettong species and is listed as ‘Near Threatened’ by the IUCN. We sequenced short read data on the 10x system to generate a reference genome 3.46Gb in size and contig N50 of 87.36Kb and scaffold N50 of 2.93Mb. Additionally, we used GeMoMa to provide and accompanying annotation for the reference genome. The generation of a reference genome for the eastern bettong provides a vital resource for the conservation of the species.